Recommendations on Surveillance for Differentiated Thyroid Carcinoma in Children with PTEN Hamartoma Tumor Syndrome. Issue 5 (28th September 2020) - Jonker, L.A.; Lebbink, C.A.; Jongmans, M.C.J.; Nievelstein, R.A.J.; Merks, J.H.M.; Nieveen van Dijkum, E.J.M.; Links, T.P.; Hoogerbrugge, N.; van Trotsenburg, A.S.P.; van Santen, H.M.
Abstract : Background: PTEN hamartoma tumor syndrome (PHTS) represents a group of syndromes caused by a mutation in the PTEN gene. Children with a germline PTEN mutation have an increased risk of developing differentiated thyroid carcinoma (DTC). Several guidelines have focused on thyroid surveillance in these children, but studies substantiating these recommendations are lacking. Objective: The present study intends to provide the available evidence for a thyroid carcinoma surveillance program in children with PHTS. Methods: An extensive literature search was performed to identify all studies on DTC in pediatric PHTS patients. Two pediatric cases are presented to illustrate the pros and cons of thyroid carcinoma surveillance. Recommendations for other patient groups at risk for DTC were evaluated. Consensus within the study team on recommendations for children with PHTS was reached by balancing the incidence and behavior of DTC with the pros and cons of thyroid surveillance, and the different surveillance methods. Results: In 5 cohort studies the incidence of DTC in childhood ranged from 4 to 12%. In total 57 cases of DTC and/or benign nodular disease in pediatric PHTS patients were identified, of which 27 had proven DTC, with a median age of 12 years (range 4–17). Follicular thyroid carcinoma (FTC) was diagnosed in 52% of the pediatric DTC patients. No evidence was found for a different clinical behavior of DTC in PHTS patients compared to sporadic DTC. Conclusions: Children with PHTS are at increased risk for developing DTC, with 4 years being the youngest age reported at presentation and FTC being overrepresented. DTC in pediatric PHTS patients does not seem to be more aggressive than sporadic DTC. Recommendations: Surveillance for DTC in pediatric PHTS patients seems justified, as early diagnosis may decrease morbidity. Consensus within the study team was reached to recommend surveillance from the age of 10 years onwards, since at that age the incidence of DTC seems to reach 5%. Surveillance for DTC should consist of yearly neck palpation and triennial thyroid ultrasound. Surveillance in children with PHTS should be performed in a center of excellence for pediatric thyroid disease or PHTS.